A Loose Legal Protection: Women Consumers’ Losses in Digital Commerce - Hakim, Faisal Luqman; Adi Sulistiyono; Suwadi, Pujiyono (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
The losses suffered by women consumers in the purchase of cosmetics and skincare products through e-commerce transactions have emerged as a critical legal issue amid the rapid expansion of digital commerce. This situation undermines public trust, particularly as women consumers often do not receive adequate legal protection due to unclear and fragmented regulatory frameworks. Examining the issue from its root causes, this study analyzes existing legal protection mechanisms for women consumers against negligence by cosmetic and skincare sellers in e-commerce transactions. The analysis draws on consumer complaints reported across various media platforms, responses from business actors, and legal actions undertaken by affected women consumers. Data were collected through documentation of printed and online media reports, court decisions, and in-depth interviews. The findings reveal that women consumers frequently suffer losses resulting from sellers’ negligence, including misleading product information, unsafe cosmetic products, and ineffective complaint-handling mechanisms. These losses are further exacerbated by the absence of clear and effective regulations governing consumer legal remedies. This article argues that the current legal framework has not yet provided optimal protection for women consumers in digital commerce. Accordingly, it recommends strengthening regulatory provisions on consumer remedies in a clearer and more concrete manner to ensure effective legal protection for women consumers in e-commerce transactions. [Kerugian yang dialami oleh konsumen perempuan dalam pembelian produk kosmetik dan perawatan kulit melalui transaksi e-commerce sering kali menjadi isu krusial seiring dengan pesatnya perkembangan perdagangan dalam dunia digital. Namun, kepercayaan publik terhadap trasaksi itu terlukai, terutama, karena konsumen perempuan kerap tidak memperoleh perlindungan hukum yang memadai akibat regulasi yang tidak jelas dan terfragmentasi. Dengan menelusuri akar permasalahan tersebut, penelitian ini menganalisis mekanisme perlindungan hukum yang tersedia bagi konsumen perempuan terhadap kelalaian pelaku usaha kosmetik dan perawatan kulit dalam transaksi e-commerce. Analisis ini didasarkan pada pengaduan konsumen yang dilaporkan melalui berbagai platform media, tanggapan dari pelaku usaha, serta upaya hukum yang ditempuh oleh konsumen perempuan yang dirugikan. Data dikumpulkan melalui dokumentasi laporan media cetak dan daring, putusan pengadilan, serta wawancara. Hasil penelitian menunjukkan bahwa konsumen perempuan kerap mengalami kerugian akibat kelalaian pelaku usaha, antara lain berupa informasi produk yang menyesatkan, peredaran produk kosmetik yang tidak aman, serta mekanisme penanganan pengaduan yang tidak efektif. Kerugian tersebut semakin diperparah oleh ketiadaan pengaturan yang jelas dan efektif mengenai upaya hukum bagi konsumen. Artikel ini berpendapat bahwa kerangka hukum yang berlaku saat ini belum memberikan perlindungan yang optimal bagi konsumen perempuan dalam perdagangan digital. Oleh karena itu, penelitian ini merekomendasikan penguatan pengaturan hukum terkait mekanisme pemulihan hak konsumen secara lebih jelas dan konkret guna menjamin perlindungan hukum yang efektif bagi konsumen perempuan dalam transaksi e-commerce.]